Workshop Mendesain Tugas Berbasis Konteks secara Kolaboratif - Rahaju, Endah Budi; Rosyidi, Abdul Haris; Prihartiwi, Nina Rinda (Universitas Nusantara PGRI Kediri, 2025)
Students need to be equipped with skills to compete globally through context-based learning. Context helps them connect math to the real world, so suitable context-based tasks can strengthen their understanding. However, the tasks designed by prospective teachers often lack of authenticity. In addition, textbooks are still lacking in presenting context-based tasks, while teachers tend to think of them as ordinary word problems. Therefore, teachers need to be given additional insights in designing context-based tasks collaboratively through community service activities for teachers. The teachers actively participated in the workshop and they felt that the workshop materials were useful for classroom learning.